STRATEGI KOMUNIKASI DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN KUANTAN SINGINGI DALAM MENINGKATKAN JUMLAH KUNJUNGAN WISATAWAN PADA AIR TERJUN GURUH GEMURAI - Fiana Desti; Muhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Tourism is one of the country's foreign exchange sources aside from the oil and gas sector potential and have the sangan large participation in building an economy that is currently pertumbuhannnya is still very slow. The tourism sector in Indonesia can still be developed with greater maximum again. The development of the tourism sector performed well will be able to attract domestic and foreign tourists to come and spend their money in the activities of berwisatanya. Of the transaction that is the community tourist areas will be elevated levels of her life as well as the State will get foreign exchange from foreign tourists exchanging currency the country with dollars.This research uses descriptive analysis with qualitative research, which emphasizes the way of view, way of life, or the taste of the disclosure of the conviction of the community with regard to issues that are examined the data, in the research the author uses descriptive research method.Based on the results of the research that researchers are doing that the Department of culture and tourism District of Kuantan Singingi should be able to manage tourism Regency kuantan singingi properly falls thunders ar tourism especially gemurai. In order for the implementation of the strategy of the promotion of tourism on the water thunders erjun gemurai this can be done by the Department of culture and tourism district of kuantan singingi in increasing the number of tourists visit and can have the prestige which is equivalent to tour the runway path, then the thing to do is to do a better promotion and build a good denngan the cooperation of various parties.